1988
DOI: 10.1161/01.res.63.3.512
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia induces changes in the level of mRNAs coding for stress protein 71 and creatine kinase M.

Abstract: Hyperthermia, hypoxia, and other conditions induce the appearance of heat shock or stress proteins in cells. We have previously shown that in the ischemic dog myocardium the level of a messenger RNA (mRNA) coding for a protein with migration characteristics similar to heat shock/stress protein 71 increases. Using a human heat-shock protein (hHSP) 70 genomic clone and anti-HSP70 antibodies as probes, we demonstrate in this report that heart stress protein (SP) 71 mRNA and its translational products (71 kDa poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(37 citation statements)
references
References 26 publications
0
37
0
Order By: Relevance
“…Cellular protein extracts were prepared as described before and the amount of TCA-precipitable cpm determined on the soluble protein fraction. Immunoprecipitation was carried out as previously described ( 12) on 106 TCA-precipitable cpm of each sample, using a polyclonal antiserum raised against a synthetic peptide identical to the COOH terminal ofthe mammalian HSP70s and HSP9Os (3). The resulting immunoprecipitated proteins were fractionated on a 8% SDS-polyacrylamide gel, fixed, enhanced, dried, and exposed to x-ray film for 14-16 h.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cellular protein extracts were prepared as described before and the amount of TCA-precipitable cpm determined on the soluble protein fraction. Immunoprecipitation was carried out as previously described ( 12) on 106 TCA-precipitable cpm of each sample, using a polyclonal antiserum raised against a synthetic peptide identical to the COOH terminal ofthe mammalian HSP70s and HSP9Os (3). The resulting immunoprecipitated proteins were fractionated on a 8% SDS-polyacrylamide gel, fixed, enhanced, dried, and exposed to x-ray film for 14-16 h.…”
Section: Methodsmentioning
confidence: 99%
“…Our laboratory ( 1,3), as well as others (2,4), have shown that at least two members ofthe heat shock protein 70 (HSP70)' kD family ofproteins are increased in their expression during ischemic damage in cardiac cells. The function of these heat shock proteins (HSPs) is mostly unknown, and only recently has it been found that the consti- 1.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…This results in an attempt by ischemic myocardiocytes to protect themselves from ischemia-reperfusion, by up-regulating the levels of stress proteins (Cornelussen et al 2003) and antioxidants (Becker 2004). Classical studies (Mehta et al 1988) showed induction of a mRNA encoding for a translation product with a molecular weight and isoelectric point similar to HSP70 in the hearts of dogs and rabbits subjected to ischemia. Knowton et al described in 1991 an ischemic preconditioning protocol consisting of 4 cycles of 5 minutes of ischemia/5 minutes of reperfusion in the anterior coronary artery of rabbits, after which an increase in m-RNA Hsp70 was detected only 1 hour after ischemia, and an increase in HSP70 was found as early as at 2 hours, although levels peaked at 24 hours.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of molecular chaperones It has been reported that synthesis of inducible forms of a major molecular chaperone, Hsp70, is increased following transient ischemic stress in the brain Nishi et al, 1993;Sharp et al, 1993;Gaspary et al, 1995), heart (Dillmann et al, 1986;Mehta et al, 1988;Knowlton et al, 1991), liver (Boeri et al, 2003;Kuboki et al, 2007) and kidney . To examine the effect of overexpression of Hsp70 in animal models of ischemic injury, three different methods were used: whole body heat stress (Marber et al, 1994), overexpression of molecular chaperones using viral vector (Yenari et al, 1998;Hoehn et al, 2001;Kelly et al, 2002) and transgenic animals expressing molecular chaperones (brain (Plumier et al, 1997;Rajdev et al, 2000;Tsuchiya et al, 2003a, b;Matsumori et al, 2005) and heart (Marber et al, 1995;Plumier et al, 1995;Radford et al, 1996;Trost et al, 1998)).…”
Section: Molecular Chaperones As Regulators Of Cell Death a Hishiya Amentioning
confidence: 99%